Inclusive versus Conventional Christian Religious Studies Curriculum for Learners with Special Needs in a Post Covid-19 Era: Teachers’ and Students’ Perspectives - Monica Nnadi, Ekwutosi; Oma Eze, Kenneth; Jacinta Oti, Chinyere; Chidi Ilechukwu, Leonard (International Journal of Psychosocial Rehabilitation, 2024)
The study emphasized the practice of inclusive curriculum as against the normal conventional Christian Religious Studies (CRS) curriculum use in the senior secondary schools. The research tried to expose the limitations of conventional curriculum on both teachers and students and had taken initiatives to advocate that curriculum planners to adapt a more learner-centered curricular. This study was found to be significant because of the exposition of various curricular activities which focused on the solutions for educating students with a wide range of differences in post Covid-19 era for greater optimization. Four research questions and two hypotheses guided the study. It adopted a descriptive research design. Purposive and simple random sampling techniques were employed in picking 35 teachers and 155 students drawn from the six education zones in Enugu state, Nigeria. The result showed that teachers strongly prefer conventional curriculum to the inclusive type; the students merely agree that conventional curriculum is preferred to them. The result also indicated that neither the subjects’ gender nor their school location influences their preference for the type of curriculum.